Branding Rhetoric in Times of a Global Pandemic: A Text-Mining Analysis. Issue 3 (21st July 2021) - Mangiò, Federico; Pedeliento, Giuseppe; Andreini, Daniela
Abstract: As the Covid-19 pandemic unfolded, academics and practitioners alike wondered how and to what extent brands should adapt their advertising and communication efforts to remain resonant and to engage their audiences. Gathering and processing a unique data set composed of about 12, 000 tweets of 76 leading brands associated with seven Italian industries, this research examines how rhetorical appeals that brands adopted evolved on Twitter during the pandemic. Theoretically, the research is grounded on an institutional logic perspective and resorts to the Aristotelian categories of logos, ethos, and pathos to make sense of the rhetorical appeals brands adopted. Methodologically, we relied on the most recent text-mining protocols in marketing studies. Our analyses outline that during the lockdown brands resorted to emotive appeals characterized by intense ethical and social overtones. Regarding consumers' response in their social media engagement, we find they appreciated this strategy the brands followed.